Infrastructuring independent cultural production : Empirical and conceptual explorations - Nehl, Marthe ; 0009-0001-0591-8537 (Lund University (Media-Tryck), 2025)
This thesis engages with the phenomenon of independent cultural production, which empirically shows itself as an idea(l) of self-determined cultural production and collaboration made possible through numerous different relationships. Independence, as a relational concept, achieved through in(ter)dependencies is what this thesis sets out to explore. Definitions of independence in cultural production are not set in stone, they allow and require cultural actors to organise themselves within a field of tension characterised by societal expectations and limited spatial, financial and personnel resources, with increasing political headwinds. Hence, turning to the conditions of independent cultural production is timely, given the rapid urban redevelopments, increasing budget cuts and curtailed freedom of expression. Theoretically, the thesis draws on the concept of infrastructure and its conceptions in both science and technology studies as well as urban and cultural studies. In the thesis, it is applied both to capture the phenomenon of independent cultural production with its conditioning relational context and to analytically unpack the processes and practices through which independence is jointly achieved, again and again. The concept carries a temporal orientation towards the long term and centres agents that maintain and care, thereby presenting a productive counterpart to the project-dominated present. Based on two case studies in the European context, and diverse datasets consisting of observations, semi-structured interviews, policy papers and archival documents, independent cultural production is realised through infrastructuring interdependencies at the local and transnational level, and the different papers examine their mutual dependence with peers and non-arts and cultural actors, in a residential neighbourhood, a transnational network, and in collaborative policy-making. At the neighbourhood level, artists and cultural workers infrastructure as they negotiate and stabilise their (spatial) conditions in service-entanglements (Paper I). At the transnational level, independent cultural centres activate and maintain communal ties as they engage in eventified network meetings, resulting in experiences of togetherness, which nourishes future infrastructuring and maintenance of a bi-annual meeting pattern providing continuity for advocacy (Paper II) and policy-making (Paper III). Paper IV draws the findings to a close and suggests the application of infrastructure through an analytical focus on practices of embedding and foregrounding, laying open the necessary and strategic practices of interrelating with people, politics, and spaces that constitute the conditions of independent cultural production.
Keywords: Independent cultural production; infrastructure; cultural network; cultural policy